Education and Language: Ethics and Language on Social Media for the Digital Generation - Soraya, Arafatul; Nasution, Asrin; Nurhalimah, Nurhalimah (Ahlussunnah: Journal of Islamic Education, 2025)
This study aims to explore ethics and language use on social media by the digital generation. Social media has become the main communication platform for this generation, but inappropriate language use and unethical behavior are often significant problems. This study uses a qualitative method, conducted by collecting data through in-depth interviews to analyze how the digital generation understands and applies ethics and chooses language in their interactions on social media. The findings show that although the digital generation has a sufficient understanding of the importance of ethics and good language, they are often caught up in social dynamics that lead to violations of ethical norms. This study also found that education and awareness of digital ethics are very important in shaping more responsible online behavior. The results of this study are expected to contribute to the development of policies and educational programs aimed at improving digital literacy and ethics among social media users.